Rethinking Old Age and Masculinity: Impact on the Re-Spatialization of Life and Research during the COVID-19 Period in Spain - Agustina Varela-Manograsso; Marcos Bote (Research on Ageing and Social Policy)
The COVID-19 pandemic and experiencing confinement resignified spaces of life and research. This experience did not affect men and women or the youth and older people in the same way. In recent years, the pandemic’s exacerbation of gender inequality and its harmful effect on the elderly have been extensively studied. However, few studies have focused on how it has impacted older men specifically, and even fewer have looked into the variations in the way they perceive their masculinity and inhabit (gendered) spaces. This paper aims to analyses that impact and those variations, as well as the research limitations that came to light in the investigation process of this study, which was also affected by restrictions imposed during the pandemic. We managed to conduct interviews and focus groups with men over 60 years old from different social backgrounds and sexual orientation to study their thoughts and beliefs about masculinity and ageing by taking into account how the re-spatialization of the participant’s lives and of the research during the pandemic transformed both the (self-)perception of masculinity and of ageing, as well as the process and results of our investigation.